2001
DOI: 10.1021/om010140x
|View full text |Cite
|
Sign up to set email alerts
|

Di-n-butyltin Methyl- and Phenylphosphonates

Abstract: The structure of [Bu 2 Sn(HO 3 PMe) 2 ] 2 (1), as determined by single-crystal X-ray diffraction, is based on a dimer containing bridging and terminal hydrogenophosphonate ligands. The tin atoms are formally five-coordinate, but exhibit also two additional remote contacts, d(Sn-O) ≈ 3.14 Å, which results in a "5+2" type coordination. This crystalline compound and the three other amorphous compounds, Bu 2 Sn(O 3 PMe) (2), Bu 2 Sn(HO 3 PPh) 2 (3), and Bu 2 -Sn(O 3 PPh) (4), have been characterized by solid state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 98 publications
5
26
0
Order By: Relevance
“…Moreover, since the X-ray diffrac- tion studies suggest that the molecule should exhibit a three line spectrum (with a 2:1:1 ratio for dipp-H, dipp-H 2 and dipp ligands, respectively), a variable temperature 31 P NMR study was carried out in the temperature range 300-243 K. The spectral pattern, however, remained the same. Thus, the presence of only two 31 P NMR signals over the entire temperature range studied suggests that the only two types of dipp-H phosphate ligands exist in the molecule in solution as has been reported for the di-n-butyltin methylphosphonate complex by Ribot et al [15] These observations have further been supported by the presence of a single broad multiplet centered at -258.7 ppm in the 119 Sn NMR spectrum of 4.…”
Section: Synthesis and Characterization Of [Nbu 2 Sn(µ-dipp-h)-(dipp-supporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, since the X-ray diffrac- tion studies suggest that the molecule should exhibit a three line spectrum (with a 2:1:1 ratio for dipp-H, dipp-H 2 and dipp ligands, respectively), a variable temperature 31 P NMR study was carried out in the temperature range 300-243 K. The spectral pattern, however, remained the same. Thus, the presence of only two 31 P NMR signals over the entire temperature range studied suggests that the only two types of dipp-H phosphate ligands exist in the molecule in solution as has been reported for the di-n-butyltin methylphosphonate complex by Ribot et al [15] These observations have further been supported by the presence of a single broad multiplet centered at -258.7 ppm in the 119 Sn NMR spectrum of 4.…”
Section: Synthesis and Characterization Of [Nbu 2 Sn(µ-dipp-h)-(dipp-supporting
confidence: 74%
“…[6] After a dormant period in between, Chandrasekhar et al [7] and others [8][9][10] showed in recent years that newer and more interesting tin aggregates and polymers could be synthesized by employing a variety of exotic and suitably designed carboxylic acids, phosphinic acids, sulfonic acids, and other acidic proton-containing main group ligands. Thus, while the interaction of both phosphinic [11][12][13] and phosphonic acids [11,[14][15][16][17] with organotin precursors in the assembly of organostannoxane cages has been a subject of intense investigation for sometime now, the use of phosphate esters for this purpose has been limited to a few sporadic reports. [18] Owing to the important role played by bulky substituents in main group chemistry in recent times, 2 ] n ·nH 2 O (3).…”
Section: Introductionmentioning
confidence: 99%
“…[20] 4 . The solid-state NMR spectra were measured using the same instrument equipped with a 4 mm MAS probe.…”
Section: Methodsmentioning
confidence: 99%
“…The solid-state NMR spectra were measured using the same instrument equipped with a 4 mm MAS probe. Crystalline NH 4 H 2 PO 4 (δ ϭ 0.95 ppm) and c-Hex 4 Sn (δ ϭ Ϫ97.35 ppm) were used as secondary references. The 119 Sn MAS NMR spectra were obtained using cross polarization (contact time 5 ms, recycle delay 10s).…”
Section: Methodsmentioning
confidence: 99%
“…Jambor et al have demonstrated that the intramolecular coordination of N,C,N-type chelating ligands to the tin center is a useful strategy for the isolation of molecular diorganotin phosphonates featuring [-Sn-O-P-O-] 2 eightmembered cyclic rings. [7] The contribution of phosphonate groups in both monoanionic and dianionic forms has been exemplified in several one-dimensional di-and triorganotin phosphonates, [8][9][10] and a layered structural motif is observed in Me 2 Sn(O 3 PPh). [11] The structure is composed of fused 12-membered tritin macrocyclic rings through bridging bidentate coordination of the phosphonate groups, and the third oxygen atom of each phosphonate provides a layered connectivity.…”
Section: Introductionmentioning
confidence: 99%